Prototype Design Of Flood Detection System Based On Arduino Uno For Home Environment - Irfan Mulya Syahputra; Rahmadani; Hafni (Cattleya Darmaya Fortuna, 2026)
Flooding is a hydrometeorological disaster that frequently occurs in Indonesia and causes significant impacts on residential areas. The limitations of early warning systems at the household scale often result in communities being late in taking preventive actions. This study aims to design and develop a prototype of a flood detection system based on Arduino Uno that is capable of providing early warnings through a buzzer and displaying water level information on an LCD. The system uses an HC-SR04 ultrasonic sensor to measure water surface levels in real time and classify them into three conditions, namely safe, alert, and danger. The research method employed is a design-and-build method with an experimental approach. Testing was conducted in a simulated environment with variations in water level up to 10 cm. The test results show that the system is able to detect changes in water level consistently with relatively small measurement deviations and provide warning responses according to the specified thresholds. This prototype is expected to serve as a simple, economical, and easily implementable solution for a flood early warning system in residential environments.